Urgensi Nilai Perusahaan: Antara Relevansi Earning Per Share, Struktur Modal dan Kebijakan Dividen - Bahtiar Effendi (Politeknik Ganesha Medan, 2023)
Firm value is one of the measurements used to gain the trust of investors and creditors. A high company value will make investors believe in investing their capital or investing in a company, because a high company value indicates high shareholder prosperity indirectly. This study aims to determine whether there is influence between earnings per share (EPS), capital structure, and dividend policy on firm value. The companies studied are consumer goods companies listed on the Indonesia Stock Exchange in 2018 – 2021. This research is a quantitative study. The population in this study is the company's consumption of goods and the sample method used is purposive sampling. The data analysis technique used is descriptive statistics, multiple linear regression analysis, coefficient of determination (R2), partial test (t test) and simultaneous test using SPSS version 26.00. The results of the study found that earnings per share and dividend policy have a significant effect on firm value, capital structure has no effect on firm value and simultaneously earnings per share, dividend policy and capital structure have a significant effect on firm value.